Relationship Between Family Functioning and Spiritual Health in Women Breast Cancer Survivors: An Analytical Cross-Sectional Study - Fatemeh Zolfaghary; Vakili Sadeghi, Mohsen; MashaghiTabari, Reza; Ali Bijani; Kheirkha, Farzan; Adib-Rad, Hajar (Shahroud Journal of Medical Sciences, 2025)
Background: Breast cancer (BC) incidence and mortality rates are on the rise, with a higher mortality rate reported in underdeveloped nations. The family practice and spiritual health have an impact on the mental well-being of BC patients. This study aimed to investigate the relationship between family practices and spiritual health among women breast cancer survivors. Methods: This analytical cross-sectional study was carried out on a sample of 96 female breast cancer (BC) survivors. In this study, a non-random convenience sampling method was employed. Data were collected using demographic and fertility checklist, the Spiritual Well-Being Scale (SWBS), and the Family Assessment Device (FAD). Results: The results of the study indicated that in the components of FAD, the general functioning subscale had the highest mean score, while the problem-solving subscale had the lowest mean score (31.26±2.14 and 12.64±1.66, respectively). The total spiritual health score was 66.27±9.62, and most women had a moderate spiritual health level (90.53%). A significant positive correlation was found between total spiritual health and age (r=0.227, P-value=0.027), along with a significant negative correlation with the roles dimension of family functioning (r=-0.233, P-value=0.023). Conclusions: This study showed that the optimal level of family functioning leads to better spiritual health in women with BC. The impact of spirituality on human beings is significant, and spiritual crises can negatively affect their physical and mental health.